Statistics for educational research simplified - Calderon, Jose F. (Ermita, Manila : Educational Publishing House, 2000)
This book, entitled Statistics for educational research simplified, has been intended particularly for graduate students who find in quite difficult to understand the more sophisticated statistical books available. The book has been limited to the more common statistical procedures used in statistically treating research data used by graduate students in preparing their research, reports, theses, and dissertation, in partial fulfillment for the requirements for their respective courses.
Part I. Definition of general terms -- Part II. Collection of data -- Part III. Descriptive statistics -- Part IV. Inferential statistics.
Includes bibliographical references and index.